High frequency trading and extreme price movements - Brogaard, Jonathan; Carrion, Allen; Moyaert, Thibaut; Riordan, Ryan; Shkilko, Andriy; Sokolov, Konstantin (Journal of Financial Economics, 2018)
Are endogenous liquidity providers (ELPs) reliable in times of market stress? We examine the activity of a common ELP type—high frequency traders (HFTs)—around extreme price movements (EPMs). We find that on average HFTs provide liquidity during EPMs by absorbing imbalances created by non-high frequency traders (nHFTs). Yet HFT liquidity provision is limited to EPMs in single stocks. When several stocks experience simultaneous EPMs, HFT liquidity demand dominates their supply. There is little evidence of HFTs causing EPMs.